IJCM_425A: Outcomes of Second Line Anti-Retroviral Therapy Among a cohort of people living with HIV/AIDS attending an ART Centre in Mangalore - Anand Nandita; Achappa Basavaprabhu; Unnikrishnan Bhaskaran; Anand Rishit (Wolters Kluwer Medknow Publications, 2024)
Background: Anti-Retroviral therapy for HIV/AIDS has been effective, but the mortality rate remains to be high, resulting in the use of second line of ART treatment for better results. Objectives: 1) To estimate the number of deaths among PLHIV between the years 2011 and 2017. 2) To assess the clinical immunological and virological outcomes among these patients. 3) To find out the association of outcomes with the socio demographic characteristics. Methods: In this record-based study, medical records of PLHIV seeking treatment from an ART center associated with KMC, Attavar. between the years 2011 and 2017 were reviewed. The data was extracted using a data extraction sheet consisting of sections on demographic, clinical and treatment details of the patient. Results: The baseline median CD4 count before starting ARTs was found to be 253 (IQR 150-351). After starting second line ARTs it was found to be 461 (IQR 326-651). The correlation of CD4 count after initiation of second line ART with viral load among 34 patients measured was found to be -0.371 (P<0.05). Conclusion: The study concludes that the outcomes of second line ARTs in the present study were found to be satisfactory. The average CD4 count after the initiation of ARTs was significantly high as compared to the CD4 count before the ARTs, implying that second line ARTs had a good, long-term and positive immunological outcome on PLHIV and attending a second-line ART clinic.